High Tax Burden Reduces Competitiveness: A Study of the Cocoa Industry in Indonesia - Murwendah; Wina Desyani (Journal of Indonesian Economy and Business, 2023)
Introduction: Due to its large production in Indonesia, cocoa beans have the potential to be one of the commodities that can increase state revenue, as they provide higher value-added than unprocessed cocoa beans. Domestic cocoa bean output has not been able to meet the needs of the domestic cocoa processing industry; hence cocoa bean imports have increased year after year. On the other hand, domestic processed cocoa producers must incur a significant tax burden to import cocoa beans. Finally, the total tax paid in the cocoa industry is substantial. It also makes domestic processed cocoa goods unable to compete with imported products. Background Problems: This study analyzes the tax policies' effects on the cocoa industry's local-oriented and export-oriented business processes. Novelty: This study provides critical insights into a comprehensive overview of tax policy on the processes of the cocoa business, whereas previous studies only addressed tax policies in one area of the cocoa industry, either the upstream, intermediate, or downstream sectors. Research Methods: This study applied a qualitative approach and collected the data through a literature study and in-depth interviews. Results: The findings revealed that tax policies on the local-oriented and export-oriented business processes of cocoa vary. The export-oriented downstream cocoa industry can utilize the facilities of a bonded zone, where the tax policy differs from that of a non-bonded zone. Conclusions: There are differences in the tax policies for cocoa's local and export-oriented business processes. The main issue for the local-oriented business processes is VAT. The imposition of VAT on cocoa beans is ultimately detrimental to farmers.